Quantum mechanics - Cohen-Tannoudji, Claude; Diu, Bernard; Laloe, Franck (New York: Wiley-Interscience, 1977)
Beginning students of quantum mechanics frequently have difficulty separating essential underlying principles from the specific examples to which these principles have historically been applied. This book is especially designed to eliminate that difficulty. Fourteen chapters, augmented by 14 "complementary sections," provide a clarity of organization, careful attention to pedagogical details, and a wealth of topics and examples that allow physics professors to tailor courses to meet students' specific needs. Each chapter starts with a clear exposition of the problem to be treated and then logically develops the physical and mathematical concept. These chapters emphasize the underlying principles of the material, undiluted by extensive references to applications and practical examples. (Such applications and practical examples are contained in the complementary sections.) The book begins with a qualitative introduction to quantum mechanical ideas using simple optical analogies and continues with a systematic presentation of the mathematical tools and postulates of quantum mechanics as well as a discussion of their physical content. Applications follow, starting with the simplest ones (two-level systems, the harmonic oscillator, etc.), and becoming gradually more complicated (the hydrogen atom, approximation methods, etc.). The complementary sections each expand this basic knowledge, supplying a wide range of applications and related topics which make use of the essential skills. Here the authors include carefully written, detailed expositions of a large number of special problems and more advanced topics-integrated as an essential portion of the text. These topics, however, are not interdependent; this allows professors to direct their quantum mechanics courses toward both physics and chemistry students.
Appendix I-III, 1457-1498p.; Bibliography 1499-1516p.; Index 1517-1524p.
Keywords: Quantum mechanics; Chemistry